2015
DOI: 10.1007/s00280-015-2769-9
|View full text |Cite
|
Sign up to set email alerts
|

Extension of the Calvert formula to patients with severe renal insufficiency

Abstract: For adult patients with severe renal insufficiency, the Calvert formula causes carboplatin overdosing by overestimating the carboplatin clearance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…It is also unclear whether this formula can be used accurately in patients with severely impaired kidney function. Furthermore, nonrenal clearance has been reported to be smaller than the constant “25” [ 116 ]. Therefore, it should be noted that carboplatin may be overdosed in patients with severely impaired kidney function because the ratio of nonrenal clearance is relatively high compared to GFR.…”
Section: Body Size Kidney Function and Clearancementioning
confidence: 99%
“…It is also unclear whether this formula can be used accurately in patients with severely impaired kidney function. Furthermore, nonrenal clearance has been reported to be smaller than the constant “25” [ 116 ]. Therefore, it should be noted that carboplatin may be overdosed in patients with severely impaired kidney function because the ratio of nonrenal clearance is relatively high compared to GFR.…”
Section: Body Size Kidney Function and Clearancementioning
confidence: 99%
“…Oguri et al 7,15 reported they had evaluated the Calvert formula in Japanese cancer patients with inulin clearance, the gold standard for the estimation of GFR. They found that the Calvert formula using GFR calculated by inulin clearance overestimated the actual carboplatin clearance with a mean prediction error of 14.3%.…”
Section: Discussionmentioning
confidence: 99%
“…However, the measured AUC in the first cycle unexpectedly exceeded the target AUC by about 20%, resulting in the development of grade 4 hematologic toxicities. A prior report concluded that Calvert’s formula causes CBDCA overdosing by overestimating CBDCA clearance in adult patients with severe renal insufficiency, including those undergoing hemodialysis, because this formula was originally developed using pharmacokinetic data from Caucasian patients with a GFR ranging from 33 to 135 mL/min [ 5 , 10 ]. This might explain why the measured AUC exceeded the target AUC in our patient, although this has not been investigated in studies with large numbers of patients.…”
Section: Discussionmentioning
confidence: 99%